Validation of the Critical-Care Pain Observation Tool (CPOT) in pediatric patients undergoing orthopedic surgery - Mandy M. J. Li; Don Daniel Ocay; Cynthia L. Larche; Kelsey Vickers; Neil Saran; Jean A. Ouellet; Céline Gélinas; Catherine E. Ferland (Canadian Journal of Pain, 2023)
ABSTRACTBackground Postoperative pain cannot be measured accurately among many children with intellectual and developmental disabilities, resulting in underrecognition or delay in recognition of pain. The Critical-Care Pain Observation Tool (CPOT) is a pain assessment tool that has been widely validated in critically ill and postoperative adults.Aims The objective of this study was to validate the CPOT for use with pediatric patients able to self-report and undergoing posterior spinal fusion surgery.Methods Twenty-four patients (10–18 years old) scheduled to undergo surgery were consented to this repeated-measure, within-subject study. To examine discriminative and criterion validation, CPOT scores and patients’ self-reports of pain intensity were collected prospectively by a bedside rater before, during, and after a nonnociceptive and nociceptive procedure on the day following surgery. Patients’ behavioral reactions were video recorded at the bedside and retrospectively viewed by two independent video raters to examine interrater and intrarater reliability of CPOT scores.Results Discriminative validation was supported with higher CPOT scores during the nociceptive procedure than during the nonnociceptive procedure. Criterion validation was supported with a moderate positive correlation between the CPOT scores and the patients’ self-reported pain intensity during the nociceptive procedure. A CPOT cutoff score of ≥2 was associated with the maximum sensitivity (61.3%) and specificity (94.1%). Reliability analyses revealed poor to moderate agreement between bedside and video raters and moderate to excellent consistency within video raters.Conclusions These findings suggest that the CPOT may be a valid tool to detect pain in pediatric patients in the acute postoperative inpatient care unit after posterior spinal fusion.